ANALISA PERSENTASE KEHILANGAN MINYAK SAWIT PADA AMPAS PRESS DI PTPN VI UNIT USAHA SOLOK SELATAN - Siregar, Muhammad Taufik; Effendi, Zulham; Mulyara, Budi; Lubis, Fadli Akbar (Jurnal Agro Fabrica, 2023)
Oil palm processing is one of the factors that determine the success of an oil palm plantation business. The Palm Oil Mill (PKS) in the context of the palm oil industry in Indonesia is understood as the unit of extraction of Crude Palm Oil (CPO) and palm kernel from the Fresh Fruit Bunches (FFB) of oil palm. The Palm Oil Mill (PKS) is the most upstream processing unit in the palm oil processing industry and is a critical point in the economic life cycle of palm fruit in particular and the palm oil industry in general. The purpose of this study was to find out how much percentage of palm oil loss was contained in the dregs of the press and to find out the optimal conditions for the screw press. The high or low percentage of oil loss in the process that occurs is influenced by several factors, namely the condition of the working pressure on the screw press and the capacity of the diluent water. The average percentage of loss of palm oil in the pressing process obtained from the data is June 5.07% with the norm of losses of pressed waste oil of 0.64%, the average of July is 4.92% with the norm of losses of pressed oil of 0, 64%, and an average of 4.98% in August with a normal loss of 0.64% of pressurized oil losses.